Feeding of the crustacean species Temora stylifera (Dana,1848)- Order Calanoida :Copepoda in the coastal waters of Baniyas City (Latakia University Journal -Biological Sciences Series, 2021)
The current research included a study of the feeding habits of a species of crustacean zooplankton of the order Calanoida, Temora stylifera (Dana, 1848), in addition to investigating the microstructure of the mandible and determining the preferred food for the species. In March and October 2020, the collection of samples was accompanied by taking hydrophysical and hydrochemical measurements from three different areas from each other with their environmental characteristics. The number of T. stylifera studied was (52) individual, of which (31) females and (21) males. The study of the shape and structure of the mandible and the gut content of the aforementioned species gave new data on the conditions and behavior of its feeding under the influence of various environmental factors. The number of phytoplankton species that appeared in gut of T. stylifera are (10) species, of which (7) belong to the phytoplankton flagellates , two species of diatoms and one species from the group Cryptophyceae. As for the average population, it was recorded (1048) individual from flagellates, followed by diatoms (402) individual, then the group of Cryptophyceae (184) individual..